Authoritarian origins of term limit trajectories in Africa. Issue 1 (2nd January 2022) - Hartmann, Christof
ABSTRACT: The article advances two related arguments with regard to term limit decisions in Sub-Saharan Africa. We should take a long-term perspective on term limit decisions and not describe and explain them as isolated events. Such a historical perspective reveals the remarkably stable patterns according to which some African countries have enforced effective term limits while others have established a tradition of circumventing them. Second, these stable term limit trajectories are shaped by the institutional legacies of different types of authoritarian regimes which had existed before 1990. Single-party authoritarian regimes have thus created a favourable institutional context for the enforcement of term limits, although through two different mechanisms. Personalist regimes, conversely, created an institutional legacy which made the continued circumvention of term limits likely. This argument is developed both theoretically and by looking at the three cases of Tanzania, Zambia and Côte d'Ivoire.